True (--sort of) - Hannigan, Katherine (New York : Greenwillow Books, 2011)
For most of her eleven years, Delly has been in trouble without knowing why, until her little brother, R.B., and a strange, silent new friend, Ferris, help her find a way to be good--and happy--again.
Keywords: Behavior -- Juvenile fiction; Selective mutism -- Juvenile fiction; Friendship -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Schools -- Juvenile fiction; Self-control -- Juvenile fiction